Transparent cap-assisted endoscopic sclerotherapy for esophageal variceal hemorrhage compared with conventional sclerotherapy: A retrospective case-control study - Zhiyong Wang; Jinlong Fu; Gang Zhou; Jianliang Wu; Liwei Sun; Yun Guo; Zhichao Lai; Sensen Tang (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Wang Z, Fu J, Zhou G, et al. Transparent cap-assisted endoscopic sclerotherapy for esophageal variceal hemorrhage compared with conventional sclerotherapy: a retrospective case-control study. Turk J Gastroenterol 2017; 28: 542-3.